Early-years future teachers’ mathematical beliefs as determinants of performance in primary mathematics - Adeneye Olarewaju Awofala; Oludola Sarah Sopekan (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2020)
One construct that lies in between the cognitive and affective domains of mathematics education is belief and this concept is rarely investigated in the Nigerian mathematics education community. Thus, an investigation of early-years future teachers’ mathematical beliefs as determinants of performance in primary mathematics within the blueprint of the quantitative method of the descriptive survey research design was conducted. Three research questions were addressed and secondary data relating to performance in mathematics of 320 early-years future teachers were retrieved from their records at the Department of Arts and Social Sciences Education, University of Lagos, Nigeria. One other instrument labeled Mathematical Beliefs Scale was employed for the collection of key data connected to the mathematical beliefs. The collected data were condensed and explored with the principal components factor analysis, multiple regression analysis, and independent samples t-test. Results showed that mathematical beliefs measured using the Mathematical Beliefs Scale are a multidimensional construct with four-factor structure: emotional and developmental commitment in learning of mathematics; self-assurance and philosophies concerning one's subjective mathematical aptitude; beliefs about mathematics; and mathematical problem-solving beliefs. These factors show adequate and excellent reliabilities as computed using Cronbach alpha. Also, gender was not a factor in early-years future teachers' mathematical beliefs even at the subscale level and the four factors of the mathematical belief scale predicted early-years future teachers' performance in primary mathematics. In line with these results, it is recommended that early-years future teachers be taught in a constructivist manner so that they can imbibe constructivist beliefs capable of engendering better learning of mathematics.